Occupational swine exposure and Hepatitis E virus, Leptospira, Ascaris suum seropositivity and MRSA colonization in Austrian veterinarians, 2017–2018—A cross‐sectional study. (16th August 2019) - Taus, Karin; Schmoll, Friedrich; El‐Khatib, Ziad; Auer, Herbert; Holzmann, Heidemarie; Aberle, Stephan; Pekard‐Amenitsch, Shiva; Monschein, Stefanie; Sattler, Tatjana; Steinparzer, Romana; Allerberger, Franz; Schmid, Daniela
Abstract: We investigated the prevalence of Hepatitis E Virus (HEV), Leptospira and Ascaris suum ( A. suum ) seropositivity, and of nasal methicillin‐resistant Staphylococcus aureus (MRSA) colonization among Austrian practising veterinarians, and assessed the association with occupational swine livestock exposure. The 261 participants completed a questionnaire on demographics, intensity of occupational swine livestock contact and glove use during handling animals and their secretions. Participants' blood samples were tested for HEV, Leptospira and A. suum seropositivity and nasal swabs cultured for MRSA. We compared swine veterinarians (defined as >3 swine livestock visits/week) to non‐swine veterinarians (≤3 swine livestock visits/week) with regard to the outcomes through calculating prevalence ratio (PR) and 95% confidence interval (CI). Furthermore, the relationship between occupational swine livestock contact and the study outcomes was examined by age (</≥55 years) and glove usage. The prevalence of nasal MRSA colonization was 13.4% (95% CI: 9.3–17.6), of HEV seropositivity 20.8% (95% CI: 15.8–25.7) and A. suum seropositivity 44% (95% CI: 37.7–50.2). The highest anti‐leptospiral antibodies titres were 1:200 ( L. hebdomadis ) and 1:100 ( L. autumnalis, L. caicola ) found in three non‐swine veterinarians. Compared to non‐swine veterinarians, swine veterinarians were 1.9 (95% CI: 1.0–3.4) and 1.5 (95%CI: 1.0–2.3) times more likely HEV seropositive and A. suum seropositive, respectively, and 4.8 (95%CI: 2.5; 9.3) times more likely nasally colonized with MRSA. Among glove‐using veterinarians, occupational swine contact was no longer a determinant for HEV seropositivity (PR 1.6; 95% CI: 0.8–2.9). Similar was found for A. suum seropositivity, which was no longer associated with occupational swine livestock contact in the subgroup of glove using, ≥55‐year‐old veterinarians (PR: 1.07; 95% CI: 0.4–3.3). Our findings indicate that >3 occupational swine livestock visits per week is associated with HEV and A. suum seropositivity and nasal MRSA colonization and that glove use may play a putative preventive role in acquiring HEV and A. suum . Further analytical epidemiological studies have to prove the causality of these associations.